Comparison of Pilates and dance aerobics on peak expiratory flow rate, body composition, and core strength in overweight and Grade 1 obese individuals - A randomized control trial - Gaurang Baxi; Ravina Randive; Divya Gohil; Soumik Basu; Tushar Palekar (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Overweight and obesity are a rapidly growing threat to health in most countries. It is an epidemic that increases the risk of diabetes, hypertension, heart disease, cancer and hence threatens to inundate health-care resources. Different form of exercises including Pilates and aerobics help improve the side effects of obesity. This study was conducted to compare the effects of Pilates and aerobics on peak expiratory flow rate (PEFR), body composition and core strength in overweight and Grade 1 obese individuals. MATERIALS AND METHODOLOGY: Thirty-three overweight and obese individuals aged 20-30 years were divided into two groups - Pilates group (n = 17) and Aerobics group (n = 16). Pilates included warm up, mat exercises, and cool down. Aerobics included warm up followed by choreographed dance, strength training, high intensity, and relaxation. PEFR by peak flow meter, body composition by body composition analyzer and core strength by pressure biofeedback were assessed, before and after the intervention. Fifty minute session were conducted thrice a week, for 4 weeks. RESULTS: Data were analyzed in the Winpepi and Primer software. Participants in both the groups showed significant improvement at the end of the study. However, the differences in between the group were not statistically significant. CONCLUSION: Pilates and aerobics are equally effective in improving the PEFR, body composition and core strength in overweight and Grade 1 obese individuals.